Mi’kmaw Women and St. Francis Xavier University’s Micmac Community Development Program, 1958-1970 - Walls, Martha (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2015)
Between 1958 and 1970 the St. Francis Xavier Extension Department operated the Micmac Community Development Program (MCDP), which aimed to bring economic development and adult education programs to Mi’kmaw communities. The MCDP had a complicated place in the lives of Mi’kmaw women. In its acceptance of racialized visions of Mi’kmaw women, its emphasis on feminine domesticity, and in its willingness to monitor Mi’kmaw families, the MCDP served the gendered and assimilative agenda of the federal state. However, its community development projects and rights-centred rhetoric also provided some Mi’kmaw women opportunities to challenge a legacy of isolating and silencing colonialism.